Aberrant Coupling Between Resting-State Cerebral Blood Flow and Functional Connectivity in Wilson’s Disease - Hu, Sheng; Wu, Hongli; Xu, ChunSheng; Wang, Anqin; Wang, Yi; Shen, Tongping; Huang, Fangliang; Kan, Hongxing; Li, Chuanfu (Frontiers in Neural Circuits, 2019)
Both abnormities of resting-state cerebral blood flow (CBF) and functional connectivity in Wilson’s disease (WD) have been identified by several studies. Whether the coupling of CBF and functional connectivity is imbalanced in WD remains largely unknown. To assess this possibility, 27 patients with WD and 27 sex- and age-matched healthy controls were recruited to acquire functional MRI and arterial spin labeling imaging data. Functional connectivity strength (FCS) and CBF were calculated based on standard gray mask. Compared to healthy controls, the CBF-FCS correlations of patients with WD were significantly decreased in basal ganglia and cerebellum, and slightly increased in prefrontal cortex and thalamus. In contrast, decreased CBF of patients with WD occurred predominately in subcortical, and cognitive- and emotional-related brain regions, including basal ganglia, thalamus, insular, and inferior prefrontal cortex, whereas increased CBF occurred primarily in the temporal cortex. The FCS decrease of WD patients was predominately in basal ganglia and thalamus, and the increase was primarily in prefrontal cortex. These findings suggest that aberrant neurovascular coupling in the brain may be a possible neuropathological mechanism underlying WD.